2001
DOI: 10.1152/ajplung.2001.280.5.l999
|View full text |Cite
|
Sign up to set email alerts
|

Release of biologically active TGF-β from airway smooth muscle cells induces autocrine synthesis of collagen

Abstract: In severe or chronic asthma, there is an increase in airway smooth muscle cell (ASMC) mass as well as an increase in connective tissue proteins in the smooth muscle layer of airways. Transforming growth factor-beta (TGF-beta) exists in three isoforms in mammals and is a potent regulator of connective tissue protein synthesis. Using immunohistochemistry, we had previously demonstrated that ASMCs contain large quantities of TGF-beta1-3. In this study, we demonstrate that bovine ASMC-derived TGF-beta associates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 35 publications
3
89
2
Order By: Relevance
“…It is possible that DC express insufficient MIF and, therefore, the MIF-related effects are not strongly mediated by these cells. Moreover, it is known that other cells such as eosinophils and airway epithelial and SMC also produce MIF (18,19) (Fig. 1B) and, therefore, the role of BMMC-or Mderived MIF in T cell activation/proliferation observed from our in vitro pure cell population assay (Fig.…”
Section: Mast Cell-derived Mif Is Required For Airway Inflammationmentioning
confidence: 77%
See 1 more Smart Citation
“…It is possible that DC express insufficient MIF and, therefore, the MIF-related effects are not strongly mediated by these cells. Moreover, it is known that other cells such as eosinophils and airway epithelial and SMC also produce MIF (18,19) (Fig. 1B) and, therefore, the role of BMMC-or Mderived MIF in T cell activation/proliferation observed from our in vitro pure cell population assay (Fig.…”
Section: Mast Cell-derived Mif Is Required For Airway Inflammationmentioning
confidence: 77%
“…1E). Another hallmark of airway inflammation is increased cell proliferation mediated by TGF-␤ from eosinophils (18) or airway SMC (19). In vitro experiments demonstrated that TGF-␤ induces MIF expression in murine colon carcinoma cells (20) and, in turn, MIF regulates TGF-␤ expression in mesangial cells (21).…”
Section: Mif-deficient Balf or Serum Contains Reduced Levels Of Chemomentioning
confidence: 99%
“…For example, increased TGF-b1 levels are associated with increased airway remodeling but decreased airways responsiveness in transgenic mice over-expressing TGFB1 in the lungs (42). In humans, TGF-b1 has been shown to stimulate increased synthesis of fibronectin/collagen (26,27), stimulate smooth muscle proliferation in the airways of people with asthma (by increasing both smooth muscle cell size and number) (43), and enhance immune responses against viral illnesses (44). Thus, genetic variants that lead to reduced levels of TGF-b1 could theoretically have paradoxical effects on airway remodeling and airway responsiveness in subjects with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of avß6 may modulate AHR by altering the expression of mast-cell proteases that can contribute to or inhibit airway narrowing (63). In addition, proteases can cleave latent TGF-b1 into its active form, inducing the synthesis of collagen in an autocrine fashion (64). Other mechanisms of TGF-b1 activation, such as ROS, mechanical stretch, contraction, and even extreme temperature changes, may also be pivotal to contributing to TGF-b1-induced fibrotic responses in asthma (Table 1).…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 99%